PENGGUNAAN TATA BAHASA BAKU DALAM PENULISAN AKADEMIK - manurung, rusdanitanelly; Fatmaira, Zira (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
In the academic world, the use of appropriate language and adherence to Indonesian grammar is crucial for conveying research effectively and clearly. The purpose of this study is to identify, analyze, and evaluate the strategic role of the use of standard grammar in academic scientific works. This study employed library research with a qualitative descriptive approach. Data were collected from various scientific literature, national and international journals, and relevant language policy documents. The study results indicate that the use of language in accordance with standard grammar avoids misunderstandings and facilitates more effective interactions between various parties, reflecting the author's professionalism and credibility in the academic environment. Therefore, standard Indonesian serves not only as a means of communication but also as an indicator of the quality of a scientific work.